ORYZA2000 v2 : a new rice crop growth simulation model for climate change studies in Africa - CGIAR Research Program on Rice (2019)
Two papers were published as shown below, and plan is to develop policy brief using these publications in 2020. van Oort, P.A.J., Zwart, S.J., 2017. Global Change Biology. van Oort P.A.J et al. 2015.PLoS ONE 10(3): e0118114.